The riddle of Lyriothemis bivittata (Rambur, 1842): Lyriothemis kameliyae spec. nov. (Odonata: Libellulidae) - Kompier, Tom (Zootaxa, 2017)
Lyriothemis kameliyae spec. nov. from northern Vietnam is described and illustrated for both sexes, and descriptions are given of male and female specimens of L. bivittata collected in Vietnam. A comparison of their distinguishing characteristics is provided, and differences from similar L. tricolor are discussed. Earlier descriptions and some records of L. bivittata are evaluated. Evidently these contain at least some L. kameliyae specimens, and therefore historic records of L. bivittata require evaluation. The ranges of the two species overlap considerably. Some information is provided on the biology of L. kameliyae.